Bilateral adrenal non-Hodgkin's lymphoma with adrenal insufficiency. Issue 898 (1st August 2000) - Ellis, R D; Read, D
Abstract : A 74 year old women presented with lethargy and weight loss and was found to have profound adrenal insufficiency and bilateral adrenal mass lesions. Histological examination revealed non-Hodgkin's lymphoma. There was no evidence of lymphoma outside the adrenal glands. Isolated bilateral adrenal masses may rarely be due to primary adrenal non-Hodgkin's lymphoma, which is often associated with adrenal insufficiency.